The role of Islamic religious counselors in preventive education against drug abuse among school-age youth in Kendari - Andi Muh. Ishak; Puti Rindang Sari; Abid Muhaimin; Zahra Shafirah Ambo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to determine the contribution of Islamic Religious Counselors through the Koran Penyuluh program in providing education on drug abuse prevention among school-age youth. This study uses a phenomenological approach from a qualitative methodology. Data in this study were collected through observation, interviews, and document studies in accordance with the research focus. Data analysis in this study was carried out in four steps, namely decontextualization, recontextualization, categorization, and compilation to identify the underlying meaning of the content. The results of this study indicate that Islamic Religious Counselors contribute positively to efforts to prevent drug abuse among school-age youth through the Koran Penyuluh; and the presence of the Koran Penyuluh provides an educational-preventive impact in the form of activities to introduce the dangers of drugs, training preachers and preachers, and several other productive activities that are constructively oriented.This is an open-access article under the CC–BY-SA license.